MANFAAT PROGRAM BAKTI BCA DARI PERSPEKTIF BENEFICIARIES PADA DIMENSI EKONOMI, SOSIAL, DAN LINGKUNGAN DI PT BANK BCA TBK (STUDI PADA PROGRAM PELATIHAN DAN PEMAGANGAN BAKTI BCA) - Hanriarseto, Tyan; Cholid, Sofyan (Jurnal Pembangunan Manusia, 2020)
The banking industry plays an important role in a country's economy and proactively engaged in CSR activities while other industries are reactive to CSR due to external stakeholder pressure (Decker, 2004). The reputation of financial institutions depends on their CSR programs (Poolthong & Mandhachitara, 2009), which is why banking institutions tend to rank high on the international CSR rating index (Perez et al., 2013). One of these challenges stems from the negative impact of individual perceptions on financial institutions' (Matute et al., 2010). This refers to the perception that each individual plays a very important role in the financial institution. One focus of Bakti BCA CSR program is education because it realizes that education is an indicator to form mental and individual character to improve social welfare. The objective of this research is to know the perception of beneficiaries of education CSR programs on CSR dimension by using quantitative research. The result of this research explained that positive perceptions of beneficiaries consisting external or internal stakeholder will have an impact on company’s operations and business. So that provides direct benefits in the social welfare of the benefits to the general public as external stakeholders and employees as internal stakeholders in order to improve the standard of living.